Convolution An Approach For Pre-auralization Of A Performance Space - Gelen, Gurur Engin (Institute of Social Sciences, 2019)
Sound is a physical phenomena. An acoustic disturbance creates vibrations which travel through a medium such as gas, liquid or solid. Due to acoustic differences in rooms, the music made in one room sounds different in another room. This change is mainly because of the acoustical response of the room and the speaker set, mixer that is used. The overall spectrum balance changes. By reflections, absorptions and diffusions sounds that are travelling in the room interfere with each other constructively and destructively in complex ways. Therefore, the overall spectrum balance changes and reverberation occurs. This thesis investigates an optimal solution to minimize the spectral difference due to room effects and playback system effects for the artists. By using a free software called REW Room Acoustics, a frequency sweep of 20Hz - 20kHz played in the room 2 times 21.8 seconds in total to calculate the response of the room. Mean response for those sweeps calculated.

Ses fiziksel bir olgudur. Akustik bir etkileşim gaz, sıvı veya katı gibi bir ortamdan geçen titreşimler yaratır. Odalardaki akustik farklılıklar nedeniyle, bir odada yapılan müzik diğer odada farklı duyulur. Bu farklılık, esas olarak odanın fiziksel özellikleri, akustik yanıtı ve kullanılan hoparlör, mikser gibi cihazların frekans yanıtlarından kaynaklanmaktadır. Bütün bunlar genel spektrum dengesini değiştirir. Yansıyan, soğurulan ve yayılan sesler karmaşık şekillerde yapıcı ve yıkıcı olarak birbirine karışır. Bu nedenle, genel spektrum dengesinde değişiklikler oluşur ve yankılanma meydana gelir. Bu tez, oda efektleri ve oynatma sistemi efektleri nedeniyle oluşan spektral farkı sanatçı açısından en aza indirmek için uygun bir çözüm araştırmaktadır. REW Room Acoustics adlı ücretsiz bir yazılım kullanarak, odanın akustik tepkisini hesaplamak için 2 kez 20Hz-20kHz aralğında olmak üzere toplamda 21.8 saniye süren bir frekans taraması yapıldı. Bu taramalar sonucunda oda özelinde ortalama frekans cevabı hesaplandı. Frekans taramalarının bir sonucu olarak bir frekans yanıt grafiği ve şelale diyagramı oluşturuldu.
Konvolusyon Performans Alanının Ön Dinlemesi Için Yaklaşım
Thesis (M.A) -- İstanbul Technical University, Institute of Social Sciences, 2019
Tez (Yüksek Lisans) -- İstanbul Teknik Üniversitesi, Sosyal Bilimler Enstitüsü, 2019
Keywords: Music; Müzik